2015
DOI: 10.1039/c4fo01059k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cholesterol and saturated fatty acid lowering by Quillaja saponaria extract, studied by in vitro digestion model

Abstract: Quillaja saponin extracts are known to reduce plasma cholesterol levels in humans. Here we study the mechanism of this effect with Quillaja Dry saponin extract (QD). In vitro model of triglyceride lipolysis is used to quantify the effect of QD on the solubilization of cholesterol and of the lipolysis products (fatty acids and monoglycerides) in the dietary mixed micelles (DMM). We found that QD extract decreases significantly both the cholesterol (from 80% to 20%) and saturated fatty acids (SFA, from 70% to 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…In previous studies, we found that QD also acts by inducing cholesterol precipitation. 25 Comparing the effects of the two extracts at similar saponin weight concentrations, one sees that QD is more efficient than SAP in decreasing cholesterol bioaccessibility. The mechanisms that govern the effect of saponins on the solubilization of cholesterol in DMM are discussed in section 4.1.…”
Section: Effects Of Saponin Extracts On the Bioaccessibility Of Chole...mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we found that QD also acts by inducing cholesterol precipitation. 25 Comparing the effects of the two extracts at similar saponin weight concentrations, one sees that QD is more efficient than SAP in decreasing cholesterol bioaccessibility. The mechanisms that govern the effect of saponins on the solubilization of cholesterol in DMM are discussed in section 4.1.…”
Section: Effects Of Saponin Extracts On the Bioaccessibility Of Chole...mentioning
confidence: 99%
“…2973) and EU (E999) and is used as an emulsifier and a foamer in several food technologies; (2) it is known to lower serum cholesterol in rats 10 and to induce cholesterol precipitation in vitro. 25 Therefore, the main purpose of the experiments with QD was to serve as a positive control, thus validating the used in vitro and in vivo methods. On the other hand, there are no reports of the effect of SAP on cholesterol and SFA, neither in vitro nor in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary fibers, specifically SDF and polyphenol, have been reported to precipitate cholesterol and bile salt (26,(32)(33)(34). In this study, AE adsorbed cholesterol micelles in vitro.…”
Section: Discussionmentioning
confidence: 87%
“…Saponins exhibit a wide range of biological activities, such as hypocholesterolemic, hypoglycemic, hepatoprotective, hemolytic, immunomodulatory, antiviral, anti-inflammatory and antitumor activities [ 15 , 16 ]. Many of these activities are usually associated with the interactions of saponins with the lipids of biological membranes, such as cholesterol and phospholipids [ 37 , 38 , 39 , 40 , 41 , 42 ]. Numerous studies have demonstrated the ability of saponins to inhibit cholesterol absorption and to decrease serum and liver cholesterol [ 43 , 44 ].…”
Section: Biological Activities Of Saponinsmentioning
confidence: 99%
“…Numerous studies have demonstrated the ability of saponins to inhibit cholesterol absorption and to decrease serum and liver cholesterol [ 43 , 44 ]. Vinarova et al recently studied the effect of six saponin extracts on the bioaccessibility of cholesterol and saturated fatty acids by using in vitro digestion model and in vivo animal studies [ 37 , 38 ]. They found that the saponin extracts (Quillaja Dry and Sapindin) can decrease cholesterol bioaccessibility up to 44%, and the main mechanism of cholesterol-lowering effect is the displacement of cholesterol from the dietary mixed micelles, which can lead to the direct precipitation of cholesterol that cannot pass through the mucus layer of the intestine.…”
Section: Biological Activities Of Saponinsmentioning
confidence: 99%